2017
DOI: 10.1002/cad.20206
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Choices in Peer Nomination Research

Abstract: Although peer nomination measures have been used by researchers for nearly a century, common methodological practices and rules of thumb (e.g., which variables to measure; use of limited vs. unlimited nomination methods) have continued to develop in recent decades. At the same time, other key aspects of the basic nomination procedure (e.g., whether nonparticipants should be included as nominees, the consequences of pairing code numbers with names on rosters) are underdiscussed and understudied. Beyond providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 53 publications
(86 reference statements)
0
78
0
3
Order By: Relevance
“…In addition to relying on self‐reports of students’ distress outcomes, the study incorporates peer‐reports of victimization and friendship. Peer nomination methods can offer an advantage over self‐report by (a) reducing potential bias in self‐perceptions and shared method variance with self‐reported outcomes; (b) more directly capturing youth's social experiences in their school contexts (Cillessen & Marks, ). Finally, we rely on a large, ethnically diverse sample to increase generalizability across demographic groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to relying on self‐reports of students’ distress outcomes, the study incorporates peer‐reports of victimization and friendship. Peer nomination methods can offer an advantage over self‐report by (a) reducing potential bias in self‐perceptions and shared method variance with self‐reported outcomes; (b) more directly capturing youth's social experiences in their school contexts (Cillessen & Marks, ). Finally, we rely on a large, ethnically diverse sample to increase generalizability across demographic groups.…”
Section: Introductionmentioning
confidence: 99%
“…Our study used two large samples and investigated relatively low levels of missingness; however, because previous studies have shown that higher levels of nonparticipation are associated with greater reductions in reliability (Marks et al, 2013) and internal validity (Babcock et al, 2018) of nomination measures, we expect that higher nonparticipation rates will result in even larger differences between including and excluding nonparticipants on rosters. Although the literature on practical solutions is sparse, Mayeux and Kraft (2017) recently suggested several strategies to deal with logistical hurdles (like low consent/participation rates) in peer nomination research.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated that the risks of being involved in sociometric research are no greater than risks faced by children and adolescents in everyday life (Mayeux et al, 2007), and the benefits of peer nomination research are substantial. Peer measurements provide a unique perspective on social behaviors among adolescents (particularly behaviors hidden from teachers or observers, such as relational aggression) and are irreplaceable to assess affective and status variables like friendship, social preference, and popularity (Cillessen & Marks, 2017). Moreover, sociometric data can play an important role in solving school problems (bullying prevention, identifying at-risk students, etc.…”
Section: Research Ethicsmentioning
confidence: 99%
“…The use of peer nominations offers several advantages over other informant reports, such as self-, parent-, or teacher-reports, and may produce a more valid assessment (Cillessen and Marks 2017). Peer nominations constitute observations from (almost) all group members and thus are not limited to one viewpoint.…”
Section: Direct Aggressionmentioning
confidence: 99%